Association of high-estimated glomerular filtration rate with the severity of ischemic stroke during non-vitamin K antagonist oral anticoagulants therapy: a nationwide cohort study - Kang, Min Kyoung; Lee, Dongwhane; Oh, Mi Sun; Lee, Ji-Sung; Jeong, Han-Yeong; Shin, Jung Hwan; Yoon, Byung-Woo; Park, Jong-Moo (Frontiers in Neurology, 2023)
Aim While the relationship between impaired kidney function and non-vitamin K antagonist oral anticoagulants (NOACs) is well established, there is limited research exploring the association between an elevated estimated glomerular filtration rate (eGFR) and the efficacy of NOACs, especially concerning the outcomes of acute ischemic stroke (AIS). This study aimed to examine the association between higher-than-normal eGFR and the severity of AIS during the use of NOACs using a nationwide multicenter stroke registry in Korea. Material and methods This study utilized data from the Korean Stroke Registry (KSR) database, examining information from 2,379 patients with AIS, who had atrial fibrillation (AF) and a history of utilizing NOACs prior to hospitalization due to incident stroke occurring between 2016 and 2021. Patients with a history involving two or more types of anticoagulants or one or more forms of antiplatelet agents were excluded. Baseline characteristics, medical history, medication usage, CHADS2-VASc score, and the anticoagulation and risk factors in atrial fibrillation (ATRIA) score were evaluated. Renal function was assessed using eGFR levels and calculated with the Cockcroft–Gault equation. The severity of stroke was measured by the National Institutes of Health Stroke Scale as an outcome. For sensitivity analysis, further evaluation was performed using eGFR levels according to the modification of diet in renal disease (MDRD) study equation. Results The mean age of subjects was 76.1 ± 8.9 years. The moderate-to-severe stroke severity group exhibited an elevation in creatinine levels. The eGFR of 60 to 89 mL/min/1.73 m2 group was associated with a decreased risk of moderate-to-severe stroke severity [hazard ratio (HR)] (0.77, 95% confidence interval (CI) [0.61, 0.98], p = 0.031) compared to the eGFR≥90 mL/min/1.73 m2 group. An increment of 10 units in eGFR was marginally associated with an increased risk of moderate-to-severe stroke severity (HR: 1.03, 95% CI [1.00, 1.07], p = 0.054). Conclusion The study revealed that individuals with eGFR ≥ 90 mL/min/1.73 m2 had an association linked to an increased risk of moderate-to-severe stroke severity. Our study suggests that patients taking NOACs with higher-than-normal eGFR levels may have an increased severity of AIS.